STRATEGI KOMUNIKASI KEPALA DESA DALAM UPAYA PENYELESAIAN KONFLIK HORIZONTAL JAMAAH SALAFI DI DESA GENTENG WETAN - Ainur Rofiq; Ahmad Irfan Ilhami (AT TAMKIN : Jurnal Pengembangan Masyarakat Islam dan Perubahan Sosial, 2023)
The purpose of this research is to find solutions related to the right village head strategy so that conflicts with salafi worshipers in Genteng Wetan Village, and empowering salafi worshipers so that conflicts with the community in Genteng Wetan Village do not occur. The research method used is qualitative with the process of data collection, data reduction, data presentation and data verification. The results of this study indicate that the village head, realising the escalation of conflict that could occur, took the initiative to initiate communication with the wahabi salafi congregation as a first step in solving this problem. The village head also proposed that the salafi wahabi congregation and the local community together find a solution that can respect the differences in views, while still maintaining harmony in the village. The communication patterns used by the village head are primary communication patterns, secondary communication patterns and linear communication patterns.